Shadow of the bird - Probert, Tim (Probert, Tim. Lightfall, 2022)
After a battle that nearly cost them their lives, Bea and Cad awaken in the hidden settlement of the Arsai, mysterious creatures who can glimpse into the future. The Arsai's vision paints a dire picture for their planet, as the bird Kest Ke Belenus--now awoken from a restless slumber--threatens to destroy all the Lights of Irpa. Desperate for a solution, Bea and Cad seek out the help of a water spirit known as Lorgon, whose ancient wisdom may help them find a way to take down Kest and save Irpa from utter destruction.